LAYOUT LENSA PROGRESSIVE UNTUK KENYAMANAN PENGGUNA - Syafril Arifin; Murni Simarmata; Lorentius Wahana Dika; Japondang Gultom (Jurnal Mata Optik, 2020)
Progressive lens is designed to make presbyopia sufferer more comfortable with their glasses as it offers sight assistance that is more natural than bifocal and trifocal do. Progressive lens can remove an object leap, better than bifocal or trifocal does. Beside, it makes vision better in near sight without turbalance in middle or far sight. However, it would not work properly without approriate setting and layout. This study uses library research in gathering relevant data and informations, desciptive approach in discussion. The main source is book authored by Icee titled “Sejarah dan Perkembangan Lensa Progressive”.